FOLKLORE IN THE WORKS OF CHINGIZ AITMATOV APPLICATION OF TRADITIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides a brief overview of the use of folklore (folklore) traditions in the works of the writer Chingiz Aitmatov.